Supplementation with inulin reverses cognitive flexibility alterations and modulates the gut microbiota in high-fat-fed mice - González-Velázquez, Gabriela; Aguirre-Garrido, José Félix; Oros-Pantoja, Rigoberto; Salinas-Velarde, Isidro Daniel; Contreras, Irazú; Estrada, José Antonio; Soto-Piña, Alexandra Estela (Frontiers in Behavioral Neuroscience, 2024)
Alterations in cognitive performance are related to inadequate nutritional states and diet composition. Prebiotics are substances that can modulate the gut microbiome and subsequently brain function through the production of metabolites such as short-chain fatty acids (SCFA). The aim of this study was to evaluate the effect of supplementation with inulin on cognitive flexibility, body composition, and the gut microbiota in a murine model exposed to a high-fat diet. CD1 mice were divided into 5 groups: Control with fed a standard diet (C), High-Fat diet (HF), Inulin (I), High-Fat diet /Inulin (HFI) and Manipulation control (M). Dietary supplementation was performed for 6 weeks. Cognitive flexibility was assessed using an Attentional Set-Shifting Test (AST). In addition, body composition was measured by electrical bioimpedance, and the adipose tissue compartments of each mouse were removed and weighed. Finally, a metataxonomic analysis of the gut microbiota was performed using bacterial 16S rRNA sequencing. Our results showed that the HF group performed more trials in the AST compared to the C, HFI, and I groups in the CD and ED stages. Interestingly, the HFI group showed decreased trials compared to the HF group in the ED stage (p = 0.0187). No significant differences in body composition were observed between groups. However, the percentage of gonadal and peritoneal adipose tissue showed significant differences in the HF and I groups compared to the C group. Statistically significant differences in alpha diversity for gut microbiota were observed using Shannon, Simpson and Chao1 indexes. The I group showed a decrease in bacterial diversity compared with the HF group. No differences were observed in the phyla Bacillota and Bacteroidetes between groups, but Clostridium bacteria represented a lower proportion of sequences in the I group than the C group. Additionally, Lactobacillus represented a lower proportion of sequences in the HF group than the C and I groups. These findings suggest that supplementation with inulin could be a useful approach to reduce the negative effects of a HF diet on cognitive flexibility and modulate the gut microbiota composition.